Republic of Kazakhstan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper discusses fiscal risk assessment in Kazakhstan. Comprehensive analysis, management, and disclosure of fiscal risks help the credibility and sustainability of public finances and supports macro stability. Risk management practices are often incomplete, fragmented, and lacking quantitative analysis. This may result in an incomplete assessment of risks with adverse impacts on activity and public finances. A more comprehensive and integrated assessment of the potential effects of shocks on public finances, in the form of fiscal analysis and stress tests, helps strengthen central forecasts and understand implications for government liquidity, financing needs, and solvency. Kazakhstan has tools to mitigate some risks, but there is not a comprehensive framework to analyze and manage all fiscal risks. The analysis of fiscal risks should be presented in a single report or statement. Enhancing monitoring, management and reporting of fiscal risks would bring considerable benefits. Best practice recommends an integrated approach to fiscal risks. A deep analysis and full disclosure following a comprehensive, integrated approach with the aim of producing a detailed fiscal risk statement in line with international best practice should be a key objective for Kazakhstan.